2020
DOI: 10.3389/fmars.2020.00048
|View full text |Cite|
|
Sign up to set email alerts
|

In the Wake of the Ongoing Mass Mortality Events: Co-occurrence of Mycobacterium, Haplosporidium and Other Pathogens in Pinna nobilis Collected in Italy and Spain (Mediterranean Sea)

Abstract: Following the Mass Mortality Events (MMEs) of the pen shell P. nobilis in Campania region and Sicily, a survey of moribund P. nobilis specimens was also conducted in other Italian regions (Campania, Tuscany, Sardinia, and Apulia) and Spain (Catalunya). Histopathological and molecular examination of 27 specimens of P. nobils revealed different types of pathogens associated with tissue lesions, morbidity and mortality. Presence of Mycobacterium, Vibrio species, Haplosporidium pinnae and Perkinsus sp. were detect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
88
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 54 publications
(99 citation statements)
references
References 50 publications
11
88
0
Order By: Relevance
“…Moreover, in accordance with what has already been suggested by Carella et al [ 19 ] (and references therein) for individuals from the northern coast of Spain and by Lattos et al [ 33 ] for Greek populations of the Thermaikos Gulf, our study further supports a hypothesis that is gaining popularity that P. nobilis mass mortality is not linked exclusively to infection by the protozoan H. pinnae [ 16 , 17 , 18 , 19 , 33 ] (and references therein). In this context, we detected no association between the occurrence of the typical signs of disease responsible for the death of individuals of P. nobilis and the presence of H. pinnae in their tissues.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Moreover, in accordance with what has already been suggested by Carella et al [ 19 ] (and references therein) for individuals from the northern coast of Spain and by Lattos et al [ 33 ] for Greek populations of the Thermaikos Gulf, our study further supports a hypothesis that is gaining popularity that P. nobilis mass mortality is not linked exclusively to infection by the protozoan H. pinnae [ 16 , 17 , 18 , 19 , 33 ] (and references therein). In this context, we detected no association between the occurrence of the typical signs of disease responsible for the death of individuals of P. nobilis and the presence of H. pinnae in their tissues.…”
Section: Discussionsupporting
confidence: 93%
“…[ 17 , 18 ], and Perkinsus spp. [ 19 ]. In the first phase of the illness, individuals affected by this unknown disease are characterized by an anomalous slow closure of the valves after external stimulation.…”
Section: Introductionmentioning
confidence: 99%
“…Taken together, these results indicate that Mycobacterium may be the leading causative in the Adriatic Sea MMEs, as suggested in recent reports [ 6 , 8 , 9 ]. It is known that pathogenic mycobacteria can undergo a prolonged asymptomatic or latent period, after which disease can be reactivated in a subset of infected hosts [ 32 , 33 ].…”
Section: Discussionsupporting
confidence: 88%
“…Additionally, during surveillance of the Seline location, strong and diffuse inflammatory lesions were observed in collected specimens without mortalities and presence of neither Mycobacterium nor Haplosporidium . It was hypothesised recently that other currently unknown causes could be involved in the pathogenesis of this disease [ 6 , 9 ]. It has also been reported that intracellular Mycobacterium may be missed by conventional ZN stain [ 37 ] and that pathogen detection may be improved by increasing the permeability of the bacterial cells with Triton-X to allow intracellular access of carbolfuchsin-dye.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation